Foreign direct investment and the welfare effects of cost harmonization - Anthony Creane; Kaz Miyagiwa (Osaka University, Institute of Social and Economic Research (ISER), 2009)
Foreign direct investment (FDI) gives foreign firms access to local labor and inputs, thereby harmonizing costs between foreign and domestic firms relative to exports. This paper investigates the welfare effects of such cost harmonization in strategic environments, finding that when the number of home firms is sufficiently close to the number of foreign firms, FDI reduces home welfare, whether FDI raises or decreases foreign firms' marginal costs. An implication is that under the same conditions, a country is harmed by tax harmonization on products that bring foreign taxes on product it imports inline with domestic ones for products.
Keywords: F12; F21; 330; foreign investment; Cournot competition; welfare